Feeding the Trolling: Understanding and Mitigating Online Trolling Behavior as an Unintended Consequence. Issue 1 (February 2022) - Golf-Papez, Maja; Veer, Ekant
Trolling is a form of consumer misbehavior that involves deliberate, deceptive, and mischievous attempts to provoke reactions from other online users. This research draws on actor-network theory to explore the assemblages of human and non-human entities that allow and perpetuate online trolling behaviors. By taking a practice-focused multi-sited ethnographic research approach, the research shows that online trolling is often an unintended consequence of interactions between human and non-human entities that are joined in the performance of trolling behavior. These entities include: troll(s), target(s), a medium of exchange, audience(s), other trolls, trolling artifacts, regulators, revenue streams, and assistants. Some of these actors (i.e., troll, target, medium) are playing a role in initiating, and other actors are (un)intentionally sustaining trolling by celebrating it, boosting it, facilitating it, and normalizing it. The findings highlight the role of nontraditional actors in the performance of misbehaviors and suggest that effective management of online consumer misbehaviors such as trolling will include managing the socio-technical networks that allow and fuel these misbehaviors.